2009
DOI: 10.1111/j.1755-0998.2009.02796.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Genetic Resources added to Molecular Ecology Resources Database 1 August 2009–30 September 2009

Abstract: This article documents the addition of 238 microsatellite marker loci and 72 pairs of Single Nucleotide Polymorphism (SNP) sequencing primers to the Molecular Ecology Resources Database. Loci were developed for the following species: Adelges tsugae, Artemisia tridentata, Astroides calycularis, Azorella selago, Botryllus schlosseri, Botrylloides violaceus, Cardiocrinum cordatum var. glehnii, Campylopterus curvipennis, Colocasia esculenta, Cynomys ludovicianus, Cynomys leucurus, Cynomys gunnisoni, Epinephelus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…All individuals were genotyped at seven microsatellite loci: C21, C30, C40, S14 (Molecular Ecology Resources Primer Development Consortium et al., 2010), Ever007, Ever009 (Holland, Dawson, Horsburgh, Krupa, & Stevens, 2013), Mic56 (This study). All loci were amplified according to the PCR protocols described in Appendix S1.…”
Section: Methodsmentioning
confidence: 53%
“…All individuals were genotyped at seven microsatellite loci: C21, C30, C40, S14 (Molecular Ecology Resources Primer Development Consortium et al., 2010), Ever007, Ever009 (Holland, Dawson, Horsburgh, Krupa, & Stevens, 2013), Mic56 (This study). All loci were amplified according to the PCR protocols described in Appendix S1.…”
Section: Methodsmentioning
confidence: 53%
“…The observed levels of population genetic structure are also consistent with other published datasets on plant metapopulations using microsatellite markers, including other Silene species. Previous research has shown that the sub-structuring of alleles is not the consequence of PCR artifacts such as null alleles [34][36]. We estimated a significantly negative Pearson product-moment correlation coefficient between the genetic diversity of individual populations and that population's contribution to F ST (r = −0.3601, 95% CI −0.6260, −0.0191; P = 0.0396; Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Our lowest F ST corresponded to the only marker composed of a dinucleotide repeat. 1 [34], 2 [35], 3 [36].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations